The effect of palm oil addition to the diet of dairy sheep on the immune response - Bianchi A.E. (2014)
The aim of this study was to evaluate whether a diet based on palm oil has any influence on the immune response and on the number of eggs per gram of faeces (EPG) of gastrointestinal nematodes (GIN) in dairy sheep. To address this issue, 30 ewes in early lactation were confined and divided into three groups (n = 10) receiving a daily isoproteic and isoenergetic diet. Palm oil was added to the feed at different concentrations: 0% (control; group A), 4% (group B) and 6% (group C). The animals were treated with levamisole 10 days before the beginning of the experiment. Faecal samples were collected and analysed for EPG on day zero of the experiment. On days 60 and 120, individual faecal and blood samples were collected, and the FAMACHA© score for assessing clinical anaemia was carried out. The groups receiving palm oil showed a significant reduction in EPG in relation to the control group (A) on day 120. Serum immunoglobulin levels (IgG, IgM and IgE) and proinflammatory cytokine levels (TNF-α, IL-1 and IL-6) were significantly increased on days 60 and 120 (p < 0.05) in groups B and C. Therefore, these results suggest that palm oil stimulates the immune response in sheep, thus reducing EPG of GIN. The hypothesis that palm oil has direct anthelmintic activity should be tested in future studies. © 2013 Blackwell Verlag GmbH.